Hubungan Pengetahuan Ibu dengan Status Gizi Balita yang Diberikan Pemberian Makanan Tambahan (PMT) Lokal di Wilayah Kerja Puskesmas Liwa - Adelia Limanda Putri; Rini Mutahar; Devieka Rhama Dhanny; Devi Ardila (Journal Malnutrition, Public Health and Local Wisdom Nutrition, 2026)
Undernutrition in children under five remains a public health problem, particularly in West Lampung Regency. Nutritional problems affect their nutritional status. Various mitigation efforts are carried out through the Local Food-Based Supplementary Feeding Program (PMT). The success of this program is influenced by several factors, one of which is maternal knowledge. The purpose of this study was to determine the relationship between maternal knowledge and the nutritional status of children under five receiving local PMT. This study used an analytic observational design with a cross-sectional approach. The population was mothers of children aged 12–59 months who participated in the local PMT program in the working area of Liwa Public Health Center. A total of 50 respondents were selected using simple random sampling with the Slovin formula. Data were collected through a knowledge questionnaire and nutritional status measurements using the weight-for-age indicator (z-score). Data were analyzed univariately and bivariately using the chi-square test. The results showed a significant relationship between maternal knowledge and nutritional status (p-value = 0.000). It can be concluded that maternal knowledge plays an important role in determining the nutritional status of children under five. Improving nutrition education is needed to support the success of the local PMT program. Keywords: children under five, local supplementary feeding, maternal knowledge, nutritional status